Awareness and Support of Clinician- and Patient-Collected Human Papillomavirus Testing for Cervical Cancer Screening Among Primary Care Clinicians - Kathy L. MacLaughlin; Robert M. Jacobson; Jennifer L. St. Sauver; Gregory D. Jenkins; Chun Fan; Lila J. Finney Rutten (Mary Ann Liebert, 2022)
Background: Cervical cancer screening has shifted toward human papillomavirus (HPV)-based testing, but uptake of primary HPV screening in the United States is unknown and previous studies highlight delays in clinician adoption of guideline updates. Methods: We conducted a cross-sectional electronic survey of primary care clinicians (n?=?252; response rate?=?30.9%) assessing awareness and support of primary HPV screening. We assessed factors for association with past use of HPV testing and support of clinician- and patient-collected HPV testing individually using Fisher's exact test and jointly using Firth's logistic regression. Results: Most clinicians (79%) were familiar with one or more primary HPV screening guidelines. Support for clinician-collected (89%) and patient-collected (82%) HPV testing was high, but only 34.5% reported prior use. Guideline familiarity was positively associated with HPV testing in practice (p?=?0.0001). Support of clinician-collected testing was positively associated with more years in practice (p?=?0.03), internal (vs. family) medicine specialty (p?=?0.03), and guideline familiarity (p???0.0001). Male clinicians more frequently supported patient collection for patients overdue for screening (p?=?0.013). Physicians more frequently than advanced practice providers (APPs) supported patient collection for screening-adherent women (p?=?0.021). Multivariable analysis showed those unfamiliar with guidelines were less likely to have used HPV testing [odds ratio, OR: 0.10 (0.03?0.32)] or to support clinician-collected HPV testing [OR: 0.16 (0.07?0.37)]. APPs were less likely than physicians to support patient-collected HPV testing among screening-adherent women [OR: 0.42 (0.20?0.87)]. Conclusions: We observed high levels of guideline awareness and clinician support for primary HPV testing, despite relatively low use. This merits further exploration to inform future interventions to increase uptake.